The Direct Pd-Catalyzed β-C(sp3)–H Activation of Carboxylic Acids - Uttry, Alexander; van Gemmeren, Manuel (Synlett, 2018)
The carboxylic acid moiety is one of the most versatile and abundant functional groups. However, despite of tremendous progress in the field of C–H functionalization reactions its use as a directing group for C(sp3)–H activation has remained limited. In this Synpact article we present the challenges associated with the carboxylic acid moiety as a native directing group and report on the newest developments in this field, including our recent study in which we developed a generally applicable protocol for the direct palladium catalyzed β-C(sp3)–H arylation of propionic acid and related α-branched aliphatic acids giving access to hydrocinnamic acids derivatives in a highly straightforward manner.1 Introduction2 Challenges in the C(sp3)–H Bond Activation of Carboxylic Acids3 History/State of the Art4 Studies towards a General β-C(sp3)–H Functionalization of Aliphatic Acids5 Conclusion
Keywords: C–H activation; carboxylic acids; arylation; palladium catalysis; propionic acid